2020
DOI: 10.3389/fpsyg.2020.01667
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Transition of the Unconscious: Automated Text Analysis of Dreams in Psychoanalytic Psychotherapy

Abstract: Aim Psychotherapy could be interpreted as a self-organizing process which reveals discontinuous pattern transitions (so-called phase transitions). Whereas this was shown in the conscious process of awake patients by different measures and at different time scales, dreams came very seldom into the focus of investigation. The present work tests the hypothesis that, by dreaming, the patient gets progressively more access to affective-laden (i.e., emotionally charged) unconscious dimensions. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…Our results support the findings of researchers who found that dreams could play a role in the reorganization of experience, particularly, in reference to memories, trauma, and the general ability of problem solving (Fosshage, 2007;. These results are in line with the studies on the psychotherapeutic process, which highlight how dream processing allows for the processing of traumatic experiences (Gennaro et al, 2020). Much research has been carried out on dreams in relation to the pandemic and the main findings highlight the central role that emotional processing plays in the dream function.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support the findings of researchers who found that dreams could play a role in the reorganization of experience, particularly, in reference to memories, trauma, and the general ability of problem solving (Fosshage, 2007;. These results are in line with the studies on the psychotherapeutic process, which highlight how dream processing allows for the processing of traumatic experiences (Gennaro et al, 2020). Much research has been carried out on dreams in relation to the pandemic and the main findings highlight the central role that emotional processing plays in the dream function.…”
Section: Discussionsupporting
confidence: 92%
“…Second, a lexical correspondence analysis (LCA)-a factor analysis procedure for nominal data (Benzécri, 1973)-has been carried out on the obtained matrix, to retrieve the factors describing lemmas having higher degrees of association, that is, occurring together many times. Each factorial dimension describes the juxtaposition of two patterns of strongly associated (co-occurring) lemmas and, according to the model grounding the analysis Gennaro et al, 2019Gennaro et al, , 2020, can be interpreted as a marker of a latent dimension of meanings underpinning dis(similarities) in the respondents' discourses and defining their SUs. The interpretation of the factorial dimensions is carried out in terms of inferential reconstruction of the global meaning envisaged by the set of co-occurring lemmas associated with each polarity, based on the abductive logic of interpretation of the relationships among single contents/lemmas (Salvatore, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In conceptualizing the human psyche as a self-organizing process revealing dynamic pattern transitions awake as much as while asleep, the dream could just be the way humans get access to more affective-loaded dimensions and meanings. Automated text-analysis and affect charge-analysis together with time-series analysis of dream narratives carried out as process analysis was able to detect the change-point in a psychotherapeutic process ( Gennaro et al, 2020 ).…”
Section: Conceptual Analysismentioning
confidence: 99%
“…Psychoanalytic work as mentioned above is concerned with memory retrieval and especially with problems in memory retrieval. The symbolic history of the subject is constituted of those contents that together form a signifying chain- with forgetting as an erasure of signifiers ( Gennaro et al, 2020 ). In current neurosciences regarding autobiographical memory a brain network consisting of the prefrontal medial (facilitating retrieval monitoring) and the posteromedial cortical brain regions (enabling the visual imagery processes of memory) has been identified ( Thome et al, 2020 ).…”
Section: Conceptual Analysismentioning
confidence: 99%